Speech Act of Demand by the Community of Speaking on the Buying Transaction of Sand Mining on the River Banks in the Sungai Sariak Region, Padang Pariaman Regency - *Vonny Ardiel; Dina Ayuning Tyas; Ira Maulina Sa'danoer; Welly Handayani; Yulia Citra; Wulandari Pertiwi; Indan Duka Lara (Universitas Syiah Kuala, 2022)
Speech Act is communication activity which contains the intent to be conveyed when speaking (the illocutionary power of an utterance) and the effect the speaker wants to achieve (perlocutionary speech). In the sale and purchase of sand mining on the banks of the Sariak River, Padang Pariaman Regency, there is a speech act between the miner and the buyer of the sand. The researcher wants to reveal the lexicon and meaning in speech acts as linguistic documentation and the richness of the lexicon. The purpose of this research is to develop linguistics in a sociopragmatic perspective. The theory used in this study is the theory of speech acts in sociopragmatic science. In this study the author uses a qualitative approach. The researcher found the syntactic aspect in the form of words and sentences. The syntactic form found is in the form of nouns that turn into adverbs due to changes in meaning in speech acts based on the context. Then find the sentence mode in the speech act of request by using declarative and interrogative sentences/questions, and using terms and language that are in accordance with the social context of interaction and culture of the community, so that efficient communication is achieved.